2020
DOI: 10.3390/jcm9041233
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of Serum Biomarkers in the Early Stages of Diabetic Retinopathy: Results of the EUROCONDOR Clinical Trial

Abstract: The main aim of this study was to evaluate the ability of serum biomarkers to predict the worsening of retinal neurodysfunction in subjects with type 2 diabetes. For this purpose, we measured selected molecules (N-epsilon-carboxy methyl lysine (CML), laminin P1 (Lam-P1), and asymmetric dimethylarginine (ADMA)) in the serum of 341 participants of the EUROCONDOR study at baseline, 24, and 48 weeks. Retinal neurodysfunction was assessed by measuring implicit time (IT) using multifocal electroretinography, and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The Consortium for the Early Treatment of DR (EUROCONDOR) study failed to find any signs of neurodegeneration in a significant percentage of patients with microangiopathic retinal lesions[ 66 , 67 ]. However, as already mentioned before, neurodegeneration has been proposed as a hallmark of DR[ 68 - 70 ].…”
Section: Experimental Data On Mechanisms Underlying the Glp-1ras/reti...mentioning
confidence: 99%
“…The Consortium for the Early Treatment of DR (EUROCONDOR) study failed to find any signs of neurodegeneration in a significant percentage of patients with microangiopathic retinal lesions[ 66 , 67 ]. However, as already mentioned before, neurodegeneration has been proposed as a hallmark of DR[ 68 - 70 ].…”
Section: Experimental Data On Mechanisms Underlying the Glp-1ras/reti...mentioning
confidence: 99%
“…Among the AGEs, the concentration of serum N-epsilon-carboxy methyl lysine (CML) and pentosidine markedly increased in both DR and DKD, especially in subjects with PDR compared to mild or severe NPDR [ 23 ]. In the EUROCONDOR trial, serum CML concentration was linked to retinal thickness and neurodysfunction, allowing for the identification of early abnormal DR findings and monitoring of its progression [ 24 ]. Elevated blood levels of RAGEs in T2DM patients with PDR compared to subjects with NPDR or without DR have also been described [ 25 ].…”
Section: Biomarkers To Predict Retinopathy In Patients With Diabetic ...mentioning
confidence: 99%
“…Previous studies have suggested the use of circulating laminin-P1 as an early marker for DR presence and severity [ 57 ]. Evidence from the EUROCONDOR showed that the baseline serum laminin-P1 was correlated to the increase in the ganglion cell layer-inner plexiform layer and overall retinal thickness [ 24 ]. Moreover, laminin-P1 was reduced in patients who were given somatostatin, indicating its usefulness in monitoring the therapeutic effectiveness of early DR management.…”
Section: Biomarkers To Predict Retinopathy In Patients With Diabetic ...mentioning
confidence: 99%
“…An ancillary study from EUROCONDOR [85] aimed to test some circulating molecules in predicting the worsening of retinal neurodysfunction. The selected molecules reflected potential biomarkers for neurodysfunction based on the NVU impairment pathogenic mechanisms.…”
Section: Serum Biomarkers and Retinal Neurodysfunctionmentioning
confidence: 99%